2008
DOI: 10.1158/0008-5472.can-07-6509
|View full text |Cite
|
Sign up to set email alerts
|

Frequently Methylated Tumor Suppressor Genes in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a very aggressive cancer. In advanced stages, the patient has poor chances of receiving effective treatment, and survival rates are low. To facilitate timely diagnosis and improve treatment, elucidation of early detection markers is crucial. DNA methylation markers are particularly advantageous because DNA methylation is an early event in tumorigenesis, and the epigenetic modification, 5-methylcytosine, is a stable mark. A genome-wide screen using Restriction La… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 20 publications
7
111
3
Order By: Relevance
“…These experiments revealed that restoring IRX1 can reduce growth and invasion of gastric carcinoma both in vitro and in vivo. The tumor suppressing function of the IRX1 gene was also confirmed by Bennett et al (2008) recently. They found that introducing IRX1 expression in squamous cell carcinoma of the head and neck disclosed the gene's tumor suppressor potential.…”
Section: Discussionmentioning
confidence: 60%
“…These experiments revealed that restoring IRX1 can reduce growth and invasion of gastric carcinoma both in vitro and in vivo. The tumor suppressing function of the IRX1 gene was also confirmed by Bennett et al (2008) recently. They found that introducing IRX1 expression in squamous cell carcinoma of the head and neck disclosed the gene's tumor suppressor potential.…”
Section: Discussionmentioning
confidence: 60%
“…Head and neck squamous cell carcinoma (HNSCC) is one of the most serious health problems, ranking as the sixth most common cancer worldwide (Bennett, 2008). Metastasis from these cancers can be fatal (Manikantan, 2012).…”
Section: Line-1 and Alu Methylation Patterns In Lymph Node Metastasesmentioning
confidence: 99%
“…[52][53][54] Although many of the novel genes we identified have not been previously reported in bladder cancer, their inappropriate methylation, accompanied with gene-silencing, has been reported in the context of other tumor types and suggests potential roles as tumor suppressor genes. 55,56,57 To determine associations between methylation and gene expression, we confined our studies to genes showing frequent and/or high mean levels of methylation. For the majority of gene-transcripts we investigated, promoter methylation was negatively correlated with reduced transcript expression, although not significantly so (data not shown).…”
Section: Discussionmentioning
confidence: 99%